2010
DOI: 10.1371/journal.pone.0014071
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Specific Adaptation in the Auditory Thalamus of the Anesthetized Rat

Abstract: The specific adaptation of neuronal responses to a repeated stimulus (Stimulus-specific adaptation, SSA), which does not fully generalize to other stimuli, provides a mechanism for emphasizing rare and potentially interesting sensory events. Previous studies have demonstrated that neurons in the auditory cortex and inferior colliculus show SSA. However, the contribution of the medial geniculate body (MGB) and its main subdivisions to SSA and detection of rare sounds remains poorly characterized. We recorded fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
274
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(292 citation statements)
references
References 65 publications
14
274
3
1
Order By: Relevance
“…This, with all caution in comparing different neural scales, makes the RP a possible human electrophysiological counterpart of SSA, with which it shares many properties: both occur without overt attention to sounds, are stimulus-specific, and develop rapidly over multiple timescales (Baldeweg, 2007;Nelken and Ulanovsky, 2007;CostaFaidella et al, 2011). Although SSA literature is overwhelming (Ulanovsky et al, 2003(Ulanovsky et al, , 2004Pérez-González et al, 2005;Reches and Gutfreund, 2008;Anderson et al, 2009;Malmierca et al, 2009;Antunes et al, 2010;Farley et al, 2010;Zhao et al, 2011), to date, no study has attempted to explore SSA-timing interactions. To confirm that an irregular timing dampens the repetition effects on a neuronal scale, further research in animal models tapping the influence of timing predictability in the generation of SSA should prove instructive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, with all caution in comparing different neural scales, makes the RP a possible human electrophysiological counterpart of SSA, with which it shares many properties: both occur without overt attention to sounds, are stimulus-specific, and develop rapidly over multiple timescales (Baldeweg, 2007;Nelken and Ulanovsky, 2007;CostaFaidella et al, 2011). Although SSA literature is overwhelming (Ulanovsky et al, 2003(Ulanovsky et al, , 2004Pérez-González et al, 2005;Reches and Gutfreund, 2008;Anderson et al, 2009;Malmierca et al, 2009;Antunes et al, 2010;Farley et al, 2010;Zhao et al, 2011), to date, no study has attempted to explore SSA-timing interactions. To confirm that an irregular timing dampens the repetition effects on a neuronal scale, further research in animal models tapping the influence of timing predictability in the generation of SSA should prove instructive.…”
Section: Discussionmentioning
confidence: 99%
“…In the auditory system, repetition suppression spans multiple spatial and time scales, as revealed by animal single-cell recordings exhibiting stimulus-specific adaptation (SSA) in cortical and subcortical structures (Ulanovsky et al, 2003(Ulanovsky et al, , 2004Pérez-González et al, 2005;Reches and Gutfreund, 2008;Anderson et al, 2009;Malmierca et al, 2009;Antunes et al, 2010;Farley et al, 2010;Zhao et al, 2011), human long-and middle-latency auditory-evoked potentials (AEP) (Haenschel et al, 2005;Slabu et al, 2010;Costa-Faidella et al, 2011;, and fMRI studies (Mutschler et al, 2010). However, none of the abovementioned studies explored the influence of timing regularity on repetition suppression, a subject lightly tapped in human electrophysiology literature, leading to contradictory findings.…”
Section: Introductionmentioning
confidence: 99%
“…In SSA, we expect a stronger response every time the sequence is switched from one stimulus to the other (lower histogram in (c)) et al 2006), and auditory (Perez-Gonzalez et al 2005) pathways. In the auditory system, neurons sensitive to deviations were found at different levels of the pathway: in the inferior colliculus, the auditory thalamus and the auditory cortex (Malmierca et al 2009;Anderson et al 2009;Farley et al 2010;Antunes et al 2010;Ulanovsky et al 2004). Detailed characterization of SSA in the auditory system revealed that it is highly sensitive to minute deviations from the standard frequency.…”
Section: Stimulus-specific Adaptationmentioning
confidence: 99%
“…The memory trace is the minimal ISI in which the response to a stimulus is not affected by it's preceding stimulus. SSA in the auditory cortex or the thalamus has been reported to diminish at ISIs longer than 2 s (Ulanovsky et al 2003) or has only been studied at ISIs < 2 s (von der Behrens et al 2009;Antunes et al 2010). Therefore, we can conclude that the information about the standard is stored in memory for only about 2 s. This poses a major problem because many examples of behavioral habituation have been reported with ISIs of tens of seconds to minutes, even for short duration stimuli (Thompson and Spencer 1966;Weinberger et al 1975;Bala and Takahashi 2000;Zimmer 2006;Glanzman 2009;Dong and Clayton 2006;Valentinuzzi and Ferrari 1997).…”
Section: The Memory Trace Problemmentioning
confidence: 99%
“…One major caveat of this hypothesis is the different time scales. Most forms of SSA were demonstrated and studied using interstimulus intervals (ISIs) of up to 2 s (Ulanovsky et al, 2003;Nelken and Ulanovsky, 2007;Reches and Gutfreund, 2008;Anderson et al, 2009;Malmierca et al, 2009;Antunes et al, 2010;Farley et al, 2010). Behavioral habituation, on the other hand, acts at ISIs of tens of seconds to minutes, even for relatively short-duration stimuli (Weinberger et al, 1975;Valentinuzzi and Ferrari, 1997;Bala and Takahashi, 2000;Zimmer, 2006;Dong and Clayton, 2009).…”
Section: Introductionmentioning
confidence: 99%